Constitutional rights of indigenous peoples in forest management in the perspective of justice - Baso Madiong (Indonesia Prime, 2021)
The Constitution of 1945 NRI mandates the protection and constitutional protection of the unity of indigenous peoples. However, the constitutional protection of indigenous peoples has not realized justice for the unity of indigenous peoples themselves. This study uses socio-legal approaches, in order to answer the problems studied. The causal factors for the realization of justice for the unity of indigenous peoples are: (1) The absence of a special law governing the unity of indigenous peoples and the diversity of the term used to mention the unity of indigenous peoples, (2) Recognition of the existence of indigenous peoples unity has not all been outlined in the regional regulations. Both reasons have an impact on conflicts that often occur between the government and the unity of indigenous peoples.